ANATOMY VISUAL LEARNING: A NEW MODALITY TO ENHANCE NEUROANATOMY LEARNING IN FIRST-YEAR MEDICAL STUDENTS - Sasanthy Kusumaningtyas; Mochamad Iskandarsyah Agung Ramadhan; Ria Margiana; Elvan Wiyarta; Reynardi Sutanto; Isabella Kurnia Liem (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2021)
Background: In gaining knowledge and comprehension of neuroanatomy, medical students require not only memorizing the anatomical structures but also understanding the spatial relationships. Along with the cadaver prosection usage, we proposed an anatomy visualization learning (AVL) as possible modality to fulfill this need, yet this has to be proven. This study aimed to know whether AVL can improve student knowledge in neuroanatomy and give a positive perception to the student. Methods: A quantitative and qualitative studies were performed to the first-year medical students (n=46) of Faculty of Medicine Universitas Indonesia who were randomly divided into two groups, an interventional (n=23) and a control (n=23) group. Both groups enrolled in the neuroanatomy learning module, with additional two sessions (two hours/session) of AVL using 3D anatomy visualization table for the intervention group. Quantitative study to know the knowledge improvement was done by comparing the pre-test, post-test and gain scores between groups. Student’s perception of the learning method was done using a questionnaire on a Likert scale. Qualitative study was done using open questions. Results: The median value of the pre-test score (8 [0-30] vs. 4 [0-42]; p=0.869) and the post-test scores (44 [30-82] vs. 40 [8-84]; p=0.068) between the interventional vs control group were not different. Nevertheless, the interventional group gained higher scores than the control group (41.6±18.06 vs. 29.8±20.47; CI 95%; p<0.05). Participants (the interventional group) had a positive perception about the AVL usage for neuroanatomy learning. Conclusion: AVL can be considered as a new approach modality for neuroanatomy learning.